Towards Digital Creativity: The Effect of Canva Application on the Creativity of Prospective Teacher Leaders - Ayu Nilna Amelia Ahmadillah; Muhammad Thohir; Alvian Nur Jamil; Koerul Li'umah (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2023)
The development of the digital creativity world has transformed the education paradigm, and aspiring teacher leaders are not left behind. In an increasingly connected world, the graphic design application Canva has become a revolutionary force that sparks their creativity. The aim of this research is to explore the influence of the Canva application on the creativity of teacher leaders. This study employed a quantitative approach with a survey method. The subjects of this research were participants of the 7th cohort of prospective teacher leaders in Bojonegoro Regency, with a population of 125 participants. A sample of 52 participants was selected using purposive sampling technique. The instrument used was a Likert-scale questionnaire. The research findings indicate that the use of the Canva application has a positive impact on the creativity of prospective teacher leaders. Based on the results of this study, it is recommended to utilize the Canva application as an effective and efficient solution to enhance the creativity of prospective teacher leaders in creating instructional content.